Biochar as a tool for effective management of drought and heavy metal toxicity. (May 2021) - Mansoor, Sheikh; Kour, Navneet; Manhas, Sweeta; Zahid, Sheikh; Wani, Owais Ali; Sharma, Vikas; Wijaya, Leonard; Alyemeni, Mohammed Nasser; Alsahli, Abdulaziz Abdullah; El-Serehy, Hamed A.; Paray, Bilal Ahmad; Ahmad, Parvaiz
Abstract: Drought and heavy metal stress undesirably disturb soil fertility and plant growth. Heavy metals pose severe biological toxic effects. Biochar, a carbon rich source application ameliorates this stress by increasing the plant growth, biomass, nutrient uptake and improves gaseous exchange in drought stress. Application of biochar reduces drought stress by increasing water holding capacity of soil through modification of soil physio-chemical properties that in turn increases water availability to plants and also enhances mineral uptake and regulation of stomatal conductance. Biochar mediates the retention of moisture, nutrients, inhibits harmful bacteria, absorbs heavy metals, pesticides, prevents soil erosion, increases soil pH, improves cationic exchange and boosts soil fertility. Drought and heavy metal stress often lead to production of reactive oxygen species. However, biochar significantly modifies the Reactive Oxygen Species (ROS) scavenging enzymes and provides an efficient electron transferring mechanism to tackle the toxic effects of ROS in plants. Biochar is regarded as a tool for the effective management of agricultural productivity and various environmental issues. This review provides insights on the potential role of biochar in ameliorating drought and heavy metal stress. Graphical abstract: Image 1 Highlights: Drought and heavy metal toxicity negatively affect soil fertility and plant growth. Biochar supplementation manages agricultural productivity and environmental issues. Application of biochar helps in modifying the physio-chemical properties of soil. Biochar application enhances water and mineral uptake and boosts soil fertility. Biochar plays a pivotal role in heavy metal remediation from contaminated soils.